2024
DOI: 10.1007/s00253-024-13040-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and population diversity of Phytophthora infestans strains in Pacific western Canada

Segun Babarinde,
Rishi R. Burlakoti,
Rick D. Peters
et al.

Abstract: Late blight caused by Phytophthora infestans is an economically important disease of potato and tomato worldwide. In Canada, an increase in late blight incidence and severity coincided with changes in genetic composition of P. infestans. We monitored late blight incidence on tomato and potato in Pacific western and eastern Canada between 2019 and 2022, identified genotypes of P. infestans, and examined their population genetic diversity. We identified four major existing genotypes US11, US17, US8, and US23 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
(218 reference statements)
0
1
0
Order By: Relevance
“…Molecular marker technology has advanced our understanding in plant pathology research [69]. Among different classes of molecular markers, SSR markers have been widely used in numerous applications in plant pathology, such as genotyping pathogen populations, genetic diversity studies, monitoring changes in pathogen populations, phylogeny, parentage analyses, and reproductive biology of various plant pathogens [6,[70][71][72][73]. This can be attributed to their multi-allelic nature, co-dominant inheritance (an important feature when analyzing the populations of diploid organisms such as P. infestans), relative abundance, repeatability, good genome coverage [74,75], and genotyping, which can be quickly completed by multiplexing all the pairs of SSR primers in a single reaction [76].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular marker technology has advanced our understanding in plant pathology research [69]. Among different classes of molecular markers, SSR markers have been widely used in numerous applications in plant pathology, such as genotyping pathogen populations, genetic diversity studies, monitoring changes in pathogen populations, phylogeny, parentage analyses, and reproductive biology of various plant pathogens [6,[70][71][72][73]. This can be attributed to their multi-allelic nature, co-dominant inheritance (an important feature when analyzing the populations of diploid organisms such as P. infestans), relative abundance, repeatability, good genome coverage [74,75], and genotyping, which can be quickly completed by multiplexing all the pairs of SSR primers in a single reaction [76].…”
Section: Discussionmentioning
confidence: 99%
“…It has the largest and most complex genome of the chromalveolates (240 megabases), with 74% of it as proliferative repetitive DNA [ 179 ]. In Canada, Babarinde et al [ 180 ] found that 25 new genotypes are emerging, as well as the already existing US11, US17, US8, and US23. Also, to illustrate this pathogen’s high evolutive ability, Shen et al [ 181 ] analysed the sequence of only one effector (Avr1) of 111 Chinese P. infestans isolates, during a short period (2010–2011), and found that nearly 80% of the isolates have undergone a point mutation.…”
Section: Genetic Methodologies For Breeding Resistance To P...mentioning
confidence: 99%